Effect of Strategic Nutrients Supplementation on Health, Productive and Reproductive Status of Crossbred Cows in Indore District of Madhya Pradesh - Sharma, Pradeep; Jain, Ravindra Kumar; Aich, Ranjit; Thakur, Dinesh (Indian Journal of Animal Nutrition, 2017)
Twenty adult healthy advanced pregnant crossbred cows (Av. BW= 418±12.67 kg) were selected randomly from the study area and feed intake of individual animal was measured to work out nutrient availability. The nutrient availability of individual animal was compared with the nutrient requirements to work out nutrient deficiencies/excess/imbalance. On the basis of results obtained, a strategic nutritional supplement was formulated. Twenty animals were divided into two groups viz., Control/un-supplemented group (n=10) fed on existing ration and treatment/supplemented group (n=10) fed on existing ration supplemented with strategic nutrients (Soya-DOC-300 g, sodium dihydrogen ortho phosphate dehydrate(NaH2PO4 .2H2O)- 11 g, zinc oxide-250 mg, copper sulphate- 169 mg, vitamin A (5 lakh IU/g) -210 mg, vitamin E 50% IU/100 g; vitamin E 50% IU/100 g) -1225 mg per head/day in gelatine capsules) during advanced pregnancy for 2 months. Results indicated shortage of DCP, TDN, P, Cu, Zn, vitamin A and vitamin E to the extent of 7.6, 4.5, 12, 48, 46, 52 and 86%, respectively. Whereas the contents of Ca, Fe, Mn, Co and Se were adequate. There were no reproductive and metabolic problems including mastitis in crossbred cows of supplemented group whereas two cows out of ten (20 %) suffered from retention of placenta, three from clinical mastitis (30 %) and two from subclinical mastitis (20 %) in the unsupplemented group. The BCS increased significantly (P<0.05) in supplemented group as compared to un-supplemented group during pre-partum period. The milk yield also increased (P<0.05) in supplemented group (8.85±0.27 L/d) as compared to unsupplemented group(6.68±0.36 L/d). It could be concluded that the strategic nutrients supplementation in the ration of advanced pregnant crossbred cows prevented reproductive problems, metabolic disorders, mastitis and improved BCS and milk yield.